Dynamic changes in the yak rumen eukaryotic community and metabolome characteristics in response to feed type - Cui, Xiaojing; Liu, Yue; Wu, Hao; Meng, Qingxiang; Liu, Shujie; Chai, Shatuo; Hao, Lizhuang; Zhou, Zhenming (Frontiers in Veterinary Science, 2022)
With diversification of yak breeding, it is important to understand the effects of feed type on the rumen, especially microbiota and metabolites. Due to the unique characteristics of yak, research on rumen microbes and metabolites is limited. In this study, the effects of two diet types on rumen eukaryotic microflora and metabolites were evaluated using the Illumina MiSeq platform and liquid chromatography-mass spectrometry (LC-MS). All identified protozoa belonged to Trichostomatia. At the genus level, the relative abundance of Metadinium and Eudiplodinium were significantly (p < 0.05) higher in the roughage group than that of concentrate group, while the concentrate group harbored more Isotricha. Ascomycota, Basidiomycota, and Neocallimastigomycota were the main fungal phyla, and the Wallemia, Chordomyces, Chrysosporium, Cladosporium, Scopulariopsis, and Acremonium genera were significantly (p < 0.05) more abundant in the roughage group than the concentrate group, while the concentrate group harbored more Aspergillus, Neocallimastix, Thermoascus, and Cystofilobasidium (p < 0.05). Metabolomics analysis showed that feed type significantly affected the metabolites of rumen protein digestion and absorption (L-proline, L-phenylalanine, L-tryosine, L-leucine, L-tryptophan, and β-alanine), purine metabolism (hypoxanthine, xanthine, guanine, guanosine, adenosine, and adenine), and other metabolic pathway. Correlation analysis revealed extensive associations between differential microorganisms and important metabolites. The results provide a basis for comprehensively understanding the effects of feed types on rumen microorganisms and metabolites of yaks. The findings also provide a reference and new directions for future research.